Board diversity and audit quality: evidence from Turkey - Mustafa, Aree S; Che Ahmad, Ayoib; Chandren, Sitraselvi (Akademia Baru, 2017)
Recent management studies report that demographic and cognitive characteristics of board of directors and corporate performance are related. [7] reported that demographic characteristics of managers influence positively on their voluntary disclosure styles.This study conjectures that demographic diversity (e.g. gender and age) and cognitive diversity (e.g. interlocking directorship and levels of education) of board of directors impacts on client’s incentive and ability to demand high audit quality proxy by Big4 auditors.Utilizing data from a sample of 415 firm-year observations for the period of 2011 to 2015 of Turkey quoted firms and using random effect estimation model to estimate the regression, we find a positive relationship between director within 36-55 and 46-55 years old and audit quality.The study’s findings also show that interlocking directorship and boards with Master degree holders has a significant positive impact on clients’ demand for high audit quality. This study contributes to provide additional theoretical insight by examining interlocking directorship with audit quality, which to the best of the researcher’s knowledge, have not been addressed in the environment of Turkey.